Macro and micro determinants of the non-performing finance: The case of Indonesian Islamic bank - Anggia Zainur Rahmah; Sheema Haseena Armina (Faculty of Economics, Universitas Islam Indonesia, 2020)
Doubtful finance showing a bad performance of a company, but this can be avoided if the banks use the right strategy to prevent such financial condition. This study aims to indicate the determinants of doubtful finance in the Indonesian Islamic banking sector from 2011 to 2018. We employed panel data regression to meet our objectives. Our results depict that banks’ profitability and finance to deposit ratio have a significant positive impact on Non-Performing Finance. On the other hand, Gross Domestic Product has a significant positive effect on doubtful finance. This study provides an alluded picture of Indonesian Islamic banking sectors, particularly Non-Performing Finance (NPF). Moreover, it enables policymakers to deliberate on the macroeconomic determinants of NPFs (i.e. GDP). Furthermore, this study will enhance the Islamic bank's performance literature.